2013
DOI: 10.1371/journal.pgen.1003378
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping and the Genomic Consequences of Selection in Sunflower

Abstract: The combination of large-scale population genomic analyses and trait-based mapping approaches has the potential to provide novel insights into the evolutionary history and genome organization of crop plants. Here, we describe the detailed genotypic and phenotypic analysis of a sunflower (Helianthus annuus L.) association mapping population that captures nearly 90% of the allelic diversity present within the cultivated sunflower germplasm collection. We used these data to characterize overall patterns of genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
131
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(145 citation statements)
references
References 56 publications
12
131
2
Order By: Relevance
“…One method of generating a high frequency of SNPs is next generation sequencing [41], [42]. Using GBS, we identified ∼35,000 polymorphic markers with a minor allele frequency>0.05.…”
Section: Discussionmentioning
confidence: 99%
“…One method of generating a high frequency of SNPs is next generation sequencing [41], [42]. Using GBS, we identified ∼35,000 polymorphic markers with a minor allele frequency>0.05.…”
Section: Discussionmentioning
confidence: 99%
“…However, GWA is not restricted to model species and is becoming increasingly widespread in nonmodel ones such as sunflower (Helianthus annuus; Mandel et al, 2013) and tomato (Solanum lycopersicum; Xu et al, 2013), where numerous associations have been successfully identified for traits related to plant architecture (branching in the case of sunflower) and fruit quality (e.g. fresh weight in tomato).…”
mentioning
confidence: 99%
“…Recent advances facilitating reverse genetics through targeted induced lesions and germline transformation will allow targeted alteration of candidate genes [19]. In addition, recently generated germplasm resources -including advanced generation recombinant inbred lines and association mapping panels [18,20] -will provide powerful tools for connecting natural allelic variation to phenotypic variation in solar tracking.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, many aspects of the physiology, development, and ecological function of solar tracking remain unexplained. Recent genetic and genomic advances [e.g., [18][19][20] poise sunflower to be a strong, tractable model system for revealing the basic mechanisms underlying growth-mediated heliotropism. Here, we review the state of our knowledge regarding solar tracking in sunflower with the purpose of highlighting open questions and raising hypotheses to be addressed by future efforts that take advantage of these new experimental resources.…”
Section: Introductionmentioning
confidence: 99%